ATUAÇÃO DA EQUIPE DE SAÚDE DA ESTRATÉGIA SAÚDE DA FAMILIA JUNTO AOS USUÁRIOS DO SISTEMA DE SAÚDE - Loro, Marli M.; Rosanelli, Cleci d. L. S. P.; Kolankiewicz, Adriane C. B.; Prauchner, Caroline K.; Kuhn, Ohana T. (Salão do Conhecimento, 2013)
Resumo